The effects of goji berry (Lycium barbarum L.) extract on some chemical, microbiological and sensory characteristics of liquid smoked common carp (cyprinus carpio L., 1758) sausages - Fadiloğlu, Eylem Ezgi; Çoban, Mehmet Zülfü (Centenary University, 2019)
In this study, the effects of goji berry extract on some quality characteristics of common carp (Cyprinus carpio L., 1758) sausages during 28 days of storage at 2±1°C were investigated. TBA (Thiobarbituric acid) values demonstrated that goji berry acted as a natural antioxidant and retarded lipid oxidation of common carp sausages during 28 days of storage. The lowest TVB-N (Total Volatile Basic Nitrogen) contents were noticed in S2 group (2% goji berry added common carp sausages) followed by S1 group (1% goji berry added common carp sausages). Total aerobic mesophilic bacteria (TAMB) of goji berry extract added samples were always lower than control samples. Goji berry extract was very effective to inhibit the growth of microorganisms. Addition of goji berry extract caused partially redness in sausage samples depending on concentration. Highest aroma and color score was found in S1 group. On the other hand, depending on increase in storage period, color and aroma scores also decreased significantly. © 2019, Centenary University. All rights reserved.
Kurt üzümü (Lycium barbarum L.) ekstraktının sazan (cyprinus carpio L., 1758) sosislerinin bazı kimyasal, mikrobiyal ve duyusal özellikleri üzerine etkileri
Keywords: Common carp sausage; Goji berry extract; Some quality parameters